PERAMALAN KURVA IPR SUMUR PADA RESERVOIR GAS KERING UNTUK KONDISI ALIRAN TURBULEN - Arief, Alpin
Gas as a low density fluid has the potential for turbulent flow in certain circumstances. In the actual conditions, the presence of turbulent flow (represented by the value of n) can affect the deliverability of a well. “n” value range between 0.5 - 1 (the value of n = 0.5 signifies that the flow is fully turbulent and the value of n close to 1 indicates laminar flow). While the constant C is influenced by factors such as viscosity and compressibility of gases whose value will change with pressure. In the future condition, as the reservoir pressure drops, the value of n and C will also changes. Therefore it is necessary to attempt to make a correlation to calculate future deliverability by comparing several parameters in the current conditions with the future conditions. The parameters used in this study is n, C and AOF. This paper studied the influence of turbulence factors in determining IPR forecasting in dry gas reservoirs. In determining the necessary parameters, well testing must be done using modified isochronal test at the same range of time. CMG Software is used for this simulation. This study use p2 method in calculating the flow rate and forchheimer coefficient factors in using non-Darcy flow. Furthermore, the value of n, C, and AOF obtained will be compared between the current states to the future states and made the correlation to the ratio of current reservoir pressure and future reservoir pressure. Dimensionless future IPR is made for forecasting IPR for any pressure drop in reservoir pressure in the reservoir model. The results obtained show that the equation of dimensionless future IPR in turbulent flow can be used to another reservoir model.